NONLINEAR RESPONSE ANALYSIS OF DOUBLE DISK RUBBING ROTOR-OIL FILM BEARING SYSTEM - LIU JunJie; ZHANG LingYun; YI FengWei; QIN ZeFeng (Jixie qiangdu)
In order to describe rotor-bearing system more accurately and to consider the influence of nonlinear oil film force and rubbing force,this paper establishes a single disk rubbing rotor-bearing system model with nonlinear support,and deduces the dimensionless motion equation of the system.The four-order runge-kutta method was used to numerically calculate the equation.The bifurcation diagram,axis trajectory diagram,Poincare cross section diagram and maximum rubbing force diagram were comprehensively used to study the dynamic behavior of the system,and the influence of eccentricity and rotation speed on the nonlinear dynamic characteristics of the system was analyzed.The analysis results show that with the decrease of eccentricity and the increase of rotating speed ratio,the rubbing force between rotating stator will also decrease,the chaotic region of the system will also decrease,and the system is in periodic motion,thus the stability of the system can be improved.